2007
DOI: 10.1021/ma0700734
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Patterns Formed by Evaporation of a Polymer Solution in the Proximity of a Sphere on a Smooth Substrate:  Molecular Weight and Curvature Effects

Abstract: A drop of polymer solution was constrained in a sphere-on-flat geometry, resulting in a liquid capillary bridge. As solvent evaporated, intriguing surface patterns of polymer formed, which were strongly dependent on the molecular weight (MW) of polymer. Dotted arrays were formed at low MW; concentric rings were produced at intermediate MW; concentric rings, rings with fingers, and punch-hole-like structures, however, were yielded at high MW. Rings with fingers as well as punch-hole-like structures were manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 28 publications
2
61
0
2
Order By: Relevance
“…The axially symmetric sphere-on-flat geometry provides a unique environment (i.e., a bound solution) for controlling the flow within an evaporating droplet, which in turn regulates the structure formation. [35][36][37][38][39][40][41] Thus, in sharp contrast to the irregular concentric rings formed due to stochastic ''stick-slip'' cycles of the contact line when a droplet evaporates from a single surface (i.e., an unbound solution), [44,45,47,48] highly ordered, gradient concentric rings of MEH-PPV are produced using the sphere-on-flat geometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The axially symmetric sphere-on-flat geometry provides a unique environment (i.e., a bound solution) for controlling the flow within an evaporating droplet, which in turn regulates the structure formation. [35][36][37][38][39][40][41] Thus, in sharp contrast to the irregular concentric rings formed due to stochastic ''stick-slip'' cycles of the contact line when a droplet evaporates from a single surface (i.e., an unbound solution), [44,45,47,48] highly ordered, gradient concentric rings of MEH-PPV are produced using the sphere-on-flat geometry.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] Rather than allowing the solvent to evaporate over the entire droplet area as in copious past work, in which droplets evaporated from a single surface, [44][45][46] the evaporation was restricted at the droplet edges. [35,36] Concentric rings were formed by controlled, repetitive pinning and depinning of the contact line (i.e., ''stick-slip'' motion).…”
Section: Introductionmentioning
confidence: 99%
“…Branching at the transition region (location 2) can be attributed mainly to the difference in height between the MEH-PPV capillary bridge under the arm and the body of the triangular-slice sphere, where H body is smaller than H arm (Figure 3 a), which led to a difference in the evaporation rate of the solvent. Because a larger capillary bridge has a higher evaporation rate, [27] the MEH-PPV meniscus beneath the arm retracted faster than that beneath the body of the triangular-slice sphere. The imbalance between the fast "stick-slip" cycles of the contact line caused by the larger capillary bridge (H arm ) and the slower "stick-slip" cycles at the smaller capillary entrance (H body ) was responsible for a locally branched pinning of the contact lines at location 2.…”
Section: Suck Won Hong Myunghwan Byun and Zhiqun Lin*mentioning
confidence: 99%
“…First, an amylose/PDP mixture was dissolved in DMSO. [33][34][35][36][37][38] Due to its higher surface tension, PDP was aggregated at the lm surface of the pores and created a ring at the rim of the pore as reported previously. Upon drying of the sample under a continuous ow of nitrogen, phase separation of the ternary amylose/PDP/DMSO solution had occurred.…”
Section: Resultsmentioning
confidence: 53%
“…Upon drying of the sample under a continuous ow of nitrogen, phase separation of the ternary amylose/PDP/DMSO solution had occurred. 18,20,21,37,39,40 The obtained ring morphology was cured into a highly crosslinked phenolic resin in the presence of formaldehyde vapor at 110 C for 5 h. 24,41,42 The cross-linked resin was carbonized under a nitrogen atmosphere at 700 C for 3 h to obtain the carbon microrings. 30 In the present study, a ring morphology was observed and the process of ring formation is believed to be caused by the two-step phase separation.…”
Section: Resultsmentioning
confidence: 99%